Synthesis of new aluminum nano hybrid composite liner for energy saving in diesel engines. (1st July 2015) - Tiruvenkadam, N.; Thyla, P.R.; Senthilkumar, M.; Bharathiraja, M.; Murugesan, A.
Highlights: Nano hybrid composite cylinder liner (NL) was developed to replace cast iron liner. NL improved engine performance, combustion and reduced emissions except NO x . Teardown analysis provides the suitability of NL for diesel engine. The developed aluminum NL saved 43.75% of weight than cast iron cylinder liner. Abstract: This work aims to replace the conventional cast iron cylinder liner (CL) in diesel engine by introducing lightweight aluminum (Al) 6061 nano hybrid composite cylinder liner (NL) by analyzing the performance, combustion, and emission characteristics of an engine. NL was fabricated by bottom pouring stir casting technique with nano- and micro-reinforcement materials. Experimental results proved that the use of NL increased brake thermal efficiency, in-cylinder pressure, heat release rate, and reduced carbon monoxide, hydrocarbon, and smoke emission in comparison with CL. However, oxides of nitrogen slightly increased with the use of the new liner. No differences in wear or other issues were noted during the engine teardown after 1 year of operation and 2000 h of running. Thus, NL has been recommended to replace the CL to save the energy and to reap environmental benefits.